The Effect of Zingiber Officinale Rosc in The Diets of Performance in Culled Layer Ducks (Faculty of Animal Science Universitas Brawijaya, 2010)
The experiment was design using a completely randomized block design (CRBD) with four treatments. Treatment were diets without Zingiber officinale rosc (A), diets contain 2,91% Zingiber officinale Rosc (B), diets contain 5,66%. Zingiber officinale Rosc (C), and diets contain 8,26% Zingiber officinale Rosc (D). Each treatment with five replicates, and each replicate consist four culled layer ducks. Variable observed were feed conversation ratio, carcass physical composition, and meat quality. It was concluded that present Zingiber officinale Rosc in the diets could be improved of performance in culled layer ducks. Keywords : Zingiber officinale Rosc, Culled layer ducks, and meat qualit